Health impact of rotavirus vaccination in China - Sharomi Oluwaseun; Chelsey Yang; Su Jian Si Tu; Jia Yin; Yan Song; Qiang Sun; Nabi Kanibir; Susanne Hartwig; Cristina Carias (Human Vaccines & Immunotherapeutics)
Rotavirus (RV) vaccines have demonstrated substantial effectiveness in reducing the healthcare burden caused by gastroenteritis (RVGE) worldwide. This study aims to understand the differential impact of RV vaccination in reducing RVGE burden in children under 7 years old in China. A Markov Model was used to investigate the health impact of introducing two different RV vaccines into the Chinese population. The analysis was conducted for RV5, a live pentavalent human-bovine reassortant vaccine, and Lanzhou Lamb RV (LLR), a live-attenuated monovalent RV vaccine, separately, by comparing the strategy of each vaccine to no vaccination within a Chinese birth cohort, including 100,000 children modeled until 7 years of age. The vaccination scenario assumed a vaccination coverage of 2.5%, 2.5%, 90% and 5% for doses one, two, three and no vaccine, respectively, for both vaccines. Strategies with RV5, LLR, and no vaccination were associated with 9,895, 49,069, and 64,746 symptomatic RV infections, respectively. RV5 and LLR were associated with an 85% and 24% reduction in the total symptomatic RV infections, respectively, suggesting that the health benefits of RV5 are at least three-fold greater than those associated with the LLR. Further, strategies with RV5 and LLR resulted in an estimated 206 and 59-year increase in quality-adjusted life years (QALYs), respectively. Sensitivity and scenario analyses supported the robustness of the base-case findings. Use of RV vaccine is expected to improve RV-associated health outcomes and its adoption will help alleviate the burden of RVGE in China. RV5 use will result in significantly better health outcomes.